Design and development of a manual breast pump : an ergonomics approach - Nur Atiqah, Ramlan (2010)
This thesis deals with design and development of a manual breast pump with an ergonomic approach. This project is the further study of the previous project which is the preliminary design of the manual breast pump. The purpose of this study is to prevent the musculoskeletal disorder problems among mothers who expressed the breast milk using manual breast pump. The objectives of this study is to design a manual breast pump with ergonomics approach using Solidworks, to make a prototype of the designed manual breast pump using Rapid Prototyping machine and to validate the designed manual breast pump using simulation process and manual calculation. The scope of this project is that the developed manual breast pump is only a prototype and is not readily functional as a commercial product. While the validations of the manual breast pump through the simulation software is considered precise. The strategy of validation of finite element analysis was developed for this project. The finite element analysis was then performed using ALGOR and the bottle part of the design was analyzed using the static stress with linear material model. The other part of the design which is the pressure pump was also manually calculated. The obtained results indicate that the maximum value of the result shows in the bottom of the bottle due to the surface boundary condition. The manual calculation of the pressure pump shows that the design just can produce the maximum pressure of about 4,000 Pa. While a good manual breast pump should produce at least about 2,000 Pa. However the area is not suitable to be reducing in a great number due to the ergonomics condition.